Greece : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2001)
This paper provides model-based projections of inflation, and quantifies the impact of the factors that determine inflation. The reasons behind the poor labor market performance in Greece and the remedial policies are discussed. The new economy is at a relatively early stage of development in Greece compared with most industrial countries, but growing rapidly. The key issues facing the Greek banking sector, against the background of its recent performance and a rapidly evolving market and regulatory environment, is discussed. The statistical data are also presented.